An evidence-based guide to combining interventions with sensory integration in pediatric practice - Blanche, Erna I. (New York : Routledge, Taylor Francis Group, 2022)
"This book offers practical ideas on the combination of sensory integration treatment principles with other evidence-based approaches in the evaluation and treatment of multifaceted issues in children with disabilities. Using the ICF Model, a Clinical Reasoning Model, and featuring numerous case studies, the opening chapters focus on combining intervention approaches with diagnoses most often encountered in clinical practice. The latter half of the book covers the research evidence supporting the delivery of services using blended intervention approaches in different settings, such as the school, the hospital and the community. Featured are five existing community programs illustrating the combination of approaches in practice. Appendices include reproducible resources a guide to assessments and approaches. The text will guide occupational therapists and other health professionals working with children and adolescents across a variety of settings in using clinical reasoning skills in a systematic manner that will lead to better interventions"--
Part 1: Foundations for Clinical Reasoning. The Pieces of the Whole -- Reasoning in Action Model (RAM): A Data-Based Model of Clinical Reasoning -- Sensory Processing: A Conceptual Model. Part 2: Pediatric Populations. Combining Approaches: Autism Spectrum Disorders -- Combining Approaches: Cerebral Palsy -- Combining Approaches: Developmental Coordination Disorder (DCD) and Other Motor Challenges -- Combining Approaches: Children Under 3 Years. Part 3: Contexts & Community Programs. Incorporating Nature in the Context of Sensory Integration Treatment -- School-Based Practice: Supporting Participation and Self-Determination -- Incorporating Sensory Integration Approaches in Pediatric Mental Health -- Provision of Occupational Therapy in the Pediatric Hospital Setting -- Mealtime Participation: Feeding and Eating Issues in Children With Neurodevelopmental Disorders -- The Context of Play -- The STAR Frame of Reference: Sensory Integration/Processing, Regulation, and Relationship -- Community Programs -- Appendices.
Includes bibliographical references and index.
Keywords: Movement disorders in children -- Treatment. -- Treatment; Sensorimotor integration